2014
DOI: 10.1111/1574-6968.12373
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of bacteria to diamond nanoparticles of various size differs in gram-positive and gram-negative cells

Abstract: In this study, the influence of the size and surface termination of diamond nanoparticles (DNPs) on their antibacterial activity against Escherichia coli and Bacillus subtilis was assessed. The average size and distribution of DNPs were determined by dynamic light scattering and X-ray diffraction techniques. The chemical composition of the DNPs studied by X-ray photoelectron spectroscopy showed that DNPs > 5 nm and oxidized particles have a higher oxygen content. The antibacterial potential of DNPs was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Shortly afterwards, Beranova et al demonstrated the inhibiting effects of detonation ND on E. coli growth [79]. The same authors reported that detonation NDs are antibacterial, while larger diamond nanoparticles obtained from milling are not [80]. This study lacked an explanation for the antibacterial properties of detonation ND, but it was suggested that untreated NDs are more effective in killing bacteria than the oxidized form.…”
Section: Inherent Antibacterial Properties Of Carbon Nanomaterialsmentioning
confidence: 97%
“…Shortly afterwards, Beranova et al demonstrated the inhibiting effects of detonation ND on E. coli growth [79]. The same authors reported that detonation NDs are antibacterial, while larger diamond nanoparticles obtained from milling are not [80]. This study lacked an explanation for the antibacterial properties of detonation ND, but it was suggested that untreated NDs are more effective in killing bacteria than the oxidized form.…”
Section: Inherent Antibacterial Properties Of Carbon Nanomaterialsmentioning
confidence: 97%
“…Nanodiamonds are biocompatible and are excellent NV carriers that can be delivered into complex biological structures including cells, organelles, and tissues [5,37,51,63]. This portability provides distinct advantages over bulk-diamond-NV centers in biological sensing.…”
Section: Introductionmentioning
confidence: 99%
“…There are advantages for using FNDs as opposed to another particle‐based labeling method, quantum dots (QD), for certain applications (Michalet et al, ). The FNDs have been reported to be generally non‐toxic, although poorly cleaned detonation nanodiamonds with varying sizes or with certain surface groups have been reported to have antibacterial properties (Beranova et al, ; Turcheniuk et al, ; Wehling, Dringen, Zare, Maas, & Rezwan, ). We use crushed high pressure high temperature (HPHT) nanodiamonds instead of detonation versions, which are cleaner to start with, then we do aggressive oxidative cleaning, which has been shown to attenuate toxicity (Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%